1999
DOI: 10.4049/jimmunol.162.7.4342
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of American Cockroach Tropomyosin (Periplaneta americana Allergen 7), a Cross-Reactive Allergen

Abstract: Inhalation of allergens produced by the American cockroach (Periplaneta americana) induces IgE Ab production and the development of asthma in genetically predisposed individuals. The cloning and expression in Escherichia coli of P. americana tropomyosin allergen have been achieved. The protein shares high homology with other arthropod tropomyosins (80% identity) but less homology with vertebrate ones (50% identity). The recombinant allergen was produced in E. coli as a nonfusion protein with a yield of 9 mg/l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Among the verified allergens, the patients showed the highest response rate to the newly identified tropomyosin, where 18 out of 20 patients had an IgE sensitivity greater than the threshold in the ELISA (Figure 2A). The significantly higher sensitization rate in these patients as compared to the 41.4% rate for the known rPer a 7 in ACR‐sensitive patients reported by WHO/IUIS Allergen Nomenclature website could be attributable to heterogeneity among the sensitization profiles of the different patient cohorts 29 …”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Among the verified allergens, the patients showed the highest response rate to the newly identified tropomyosin, where 18 out of 20 patients had an IgE sensitivity greater than the threshold in the ELISA (Figure 2A). The significantly higher sensitization rate in these patients as compared to the 41.4% rate for the known rPer a 7 in ACR‐sensitive patients reported by WHO/IUIS Allergen Nomenclature website could be attributable to heterogeneity among the sensitization profiles of the different patient cohorts 29 …”
Section: Resultsmentioning
confidence: 73%
“…Our high-quality genome (3.06 Gb) and precisely annotated proteome (29,939) of the American cockroach help revealed a broader allergen spectrum. Seven novel allergen groups Per a 14 to Per a 20 and one isoallergens (Per a 7.02) were validated using ELISA in Thai cohort.…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 25 years, several important CR allergens have been purified and characterized; they can now be used for the systematic assessment of the sensitization profiles of allergic individuals. 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 Component-resolved diagnosis allows for distinguishing between genuine sensitizations, cosensitizations, and cross-reactivities for different allergen sources. 29 With this approach, it has been shown that CR-allergic patients present variable sensitization profiles, without defined immunodominant major CR allergens.…”
mentioning
confidence: 99%
“…Moreover, strong IgE cross-reactivity between CR, HDM, and shellfish allergens has been described, in manycases mediated by pan-allergens, such as tropomyosins or arginine kinases. 25 , 27 , 33 …”
mentioning
confidence: 99%